Using Board Games Activities in Developing Iraqi EFL Preparatory School Students' Performance in Reading Skills - Mohammed Jassim Hussein; Ahmed Rudhwan Selman; Abd Ali Nayef Hassan (Sociometry Journal of Social Science, Art and Humanity, 2021)
Learning a second language can be challenging and demanding, especially for teachers, as they are required to continuously innovate and improve their teaching by integrating new strategies and techniques into the classroom environment. Hence, the present study intents to examine the effect of board games activities on Iraqi Preparatory school students’ reading skills. A quantitative research method is adopted, and a sample of (30) preparatory school students is randomly chosen to exemplify the two sets of the research (the control and experimental groups). The study adopts a pre-test post-test design to measure the influence of the strategy. The first hypothesis is accepted, and the researcher concluded that indeed board games activities help in developing the students’ reading skills; however, other studies could concur or find different results.